ANALISIS PENGARUH PROFITABILITAS INDUSTRI, RASIO LEVERAGE KEUANGAN TERTIMBANG, RASIO INTENSITAS MODAL TERTIMBANG DAN PANGSA PASAR TERHADAP ROA DAN ROE PERUSAHAAN MANUFAKTUR YANG GO-PUBLIC DI INDONESIA - Tiyas Maya Listyawati; Hani Sirine (AKSES: Jurnal Ekonomi dan Bisnis, 2007)
This research investigates four proxies of competitive ratio that being influence to the company profitability. These proxies are industry profitability, weighted leverage, weighted capital intensiveness, and market share. The sample employed in the present study consist of the 54 firm, which have been listed at Jakarta Stock Exchange since 1999. The annual financial report data employed spans the years 1999-2004. The z test is used to test hypothesis.Research findings show that, first industry profitability, weigted leverage, and capital intensiveness are statistically significant to influence return on asset. Second, industry profitability and weighted capital intensiveness are statistically significant to influence return on equity. Third, regression model of ROA has R2 higher than regression model of ROE. This result indicates that ROA model is more robust than ROE model.Keywords:  Return on asset, return on equity, industry ratio.